Integrating Students’ Creative Soft Skill In Mathematics Learning Media Development - Farit Dwi Ratnasari; Wiwin Sri Hidayati; Abdul Rozak (Pi: Mathematics Education Journal, 2026)
The purpose of this study was to determine the integration of students' creative soft skills in developing mathematics learning media. This type of research is descriptive qualitative. The subjects of this study were groups of 4 fifth-semester students of the Mathematics Education Study Program, PGRI Jombang University. The instruments used were creativity observation sheets and interview guidelines. Data collection techniques used observation and interviews. Data analysis techniques consisted of reducing data from the observation sheets and interviews. Then presenting the collected data for analysis and drawing conclusions. The results of the study showed that creativity was reflected in three aspects: originality, flexibility, and fluency in developing learning media. Students were able to produce innovative media concepts, develop ideas, and design according to students' needs. These three aspects of creativity indicate that student creativity is able to develop innovative and meaningful learning media. Strengthening creativity prepares teachers to be more responsive to students' learning needs.